A cadeia produtiva de soja e o desenvolvimento econômico e regional no Brasil - José Eustáquio Ribeiro Vieira Filho (Instituto de Pesquisa Econômica Aplicada (IPEA), 2024)
– This study shows the importance of soybean production in Brazilian economic development. Three blocks of data were studied: i) the soy production chain and added value; ii) regional production and human development indexes; and iii) international trade and food security. The study demystifies three myths. The first is to believe that soybean production generates low added value. This assertion is false, since soy is a strategic input in several production chains. The second is to believe that the growth in soybean production has little effect on local development. The sector's productive dynamics are capable of attracting more and more population and specialized work, as well as incorporating science and technology. The third myth is to imagine that increased exports harm the country's food security. This fact was not observed over time by the increase of per capita consumption of various food products derived from soybeans chain, even with the growth of exports on the international market.
Keywords: O1; O2; O4; 330; productivity; agriculture; growth; soybean